2019
DOI: 10.1002/cncr.32403
|View full text |Cite
|
Sign up to set email alerts
|

Microbial characterization of esophageal squamous cell carcinoma and gastric cardia adenocarcinoma from a high‐risk region of China

Abstract: Background Little is known about the microbiota and upper gastrointestinal tumors. Esophageal squamous cell carcinoma (ESCC) and gastric cardia adenocarcinoma (GCA) occur in adjacent organs, co‐occur geographically, and share many risk factors despite being of different tissue types. Methods This study characterized the microbial communities of paired tumor and nontumor samples from 67 patients with ESCC and 36 patients with GCA in Henan, China. DNA was extracted with the MoBio PowerSoil kit. The V4 region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
86
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 44 publications
(83 reference statements)
16
86
2
1
Order By: Relevance
“…In our study, Proteobacteria, Firmicutes, Bacteroidetes, and Fusobacterium were the most dominant phyla in case and control groups. Comparison with the previous research ndings, Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria was identi ed as the most dominant phyla in the gastric environment which shows consistent results with the current study [19,22,[37][38][39]. A study conducted using Chinese and Mexican populations revealed that HP was the predominant member of the microbiota in the gastric environment [40].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, Proteobacteria, Firmicutes, Bacteroidetes, and Fusobacterium were the most dominant phyla in case and control groups. Comparison with the previous research ndings, Proteobacteria, Firmicutes, Bacteroidetes, Actinobacteria, and Fusobacteria was identi ed as the most dominant phyla in the gastric environment which shows consistent results with the current study [19,22,[37][38][39]. A study conducted using Chinese and Mexican populations revealed that HP was the predominant member of the microbiota in the gastric environment [40].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, some of recent epidemiological studies have suggested the involvement of gastric microbiome in GC occurrence by the induction of chronic in ammation or down regulation of host immunity [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…41 An association of Fusobacterium nucleatum, one of the periodontal bacteria, with the risk of colorectal cancer has been proven. 42 Another study by Shao et al 31 evaluated the difference in the esophageal microbiome between patients with ESCC and those with gastric cardia adenocarcinoma (GCA). Patients with ESCC showed a high proportion of Fusobacteria phylum (ESCC: 3.9% and GCA: 1.9%).…”
Section: Esophageal Cancer and Esophageal Microbiomementioning
confidence: 99%
“…Yamamura et al reported that DNA levels of F. nucleatum in esophageal cancer tissues were higher than those in pared adjacent non-tumor tissues [ 47 ]. Moreover, esophageal squamous cell carcinoma (ESCC) tissues contained more Fusobacterium (3.2% vs. 1.3%) and less Streptococcus (12.0% vs. 30.2%), compared to the non-tumor tissues [ 48 ]. Importantly, higher DNA levels of F. nucleatum in ESCC patients were significantly associated with cancer-specific survival [ 47 ], predicted poor recurrence-free survival, and poor response to neoadjuvant chemotherapy [ 49 ].…”
Section: F Nucleatum and Cancermentioning
confidence: 99%